Optimization of cu2o and cuscn as htl of planar perovskite solar cells via numerical simulation - Kothandapani Z.; Islam M.A.; Reza Y.; Hasan A.A.Q.; Alkahtani A.A.; Amin N. (S.C. Virtual Company of Phisics S.R.L, 2023)
Perovskite solar cells have gained a great deal of interest as it has low cost, suitable electronic and optical properties, and strong light absorption. Since the replacement of liquid electrolyte in 2012, there has been a need to optimize the Hole Transport Layer (HTL) to achieve higher efficiency. Copper Thiocyanate (CuSCN) and Cuprous Oxide (Cu2O) are inorganic HTLs, which have a bandgap of 3.4eV and 2.17eV respectively are abundant, non-toxic, and suitable for band matching. Using CuSCN and Cu2O as an electron blocking layer allows for reducing manufacturing cost and improving solar cell performance. Inorganic HTLs such as CuI and NiO are proven to have good stability, low cost, and high mobility. Currently, organic HTLs such as Spiro MeOTAD produce higher efficiency, however, they have poor thermal stability. This work looks into optimizing the CuSCN and Cu2O as an HTL to replace the expensive Spiro MeOTAD, which incurs high manufacturing costs. Using SCAPS-1D software, an efficiency of 21.5% was achieved by varying the parameters of the HTL and absorber layer. The results indicate that CuSCN is a better HTL compared to Cu2O. 2020, S.C. Virtual Company of Phisics S.R.L. All rights reserved.